Formation of conidia in a saprophytic strain Claviceps paspali producing simple lysergic acid derivatives - Rylko, V; Linhartová, R; Sajdl, P; Rehácek, Z (Folia microbiologica, 1988)
A non-mutant saprophytic strain C. paspali which forms conidia both on a solid medium and during submerged fermentation is described. Conidiation proceeded in parallel with culture growth and production of alkaloids. The effect of composition of culture media on the intensity of conidiation is described.
Keywords: časové faktory; kultivační média; Claviceps; kyselina lysergová; Spores; spory; Lysergic Acid; Time Factors; ergoliny; Culture Media; Ergolines